Elevated Blood Pressure in Women of Childbearing Age in the United States. Issue 1 (January 2022) - Logsdon, M. Cynthia; Blair, Leeanna; Gunaratnam, Bakeerathan
Abstract: Purpose: Elevated blood pressure is frequently associated with adverse health issues among women during and after childbirth in the United States. The purpose of this study was to describe incidence of and determine predictors of prehypertension and hypertension among women of childbearing age in the United States. Study Design and Methods: Using secondary data analysis, existing data from the National Health and Nutrition Examination Survey (NHANES; 2013-2018 ) were used to address study aims. Inclusion criteria were women in the age range commonly considered to be of childbearing age, 15 to 44 years of age. Simple random sampling was to select subjects from the 2, 932 women in the NHANES dataset who met inclusion criteria. We calculated a sample size as adequate for the statistical group comparison to be significant with a power of 95% to detect a difference among groups. An ordinal logistic regression model was created to discriminate predictors of normotensive blood pressure, prehypertension, and hypertension. Results: The sample ( n = 393) included 300 women with normal blood pressure, 46 women with prehypertension, and 47 with hypertension. Older women (within childbearing age range), women with high body mass index, and African American women are highly likely to have prehypertension and hypertension. Clinical Implications: Contrary to previous research, poverty income ratio was not associated with prehypertension and hypertension. Future research should test interventions that include promoting heathy lifestyles and address elevated body mass index. Interventions should be tailored to be culturally appropriate for African American women and older women within this age range. Abstract : Hypertension is more prevalent among women who identify as African American when compared to other ethnic or racial groups and is a risk factor for adverse pregnancy, childbirth, postpartum, and later life outcomes, In this study of women's health data from a national data base, older women (at the highest range of childbearing age), women with a high body mass index, and women who self-identified as African American were more likely to have prehypertension and hypertension. Nursing care for women during the childbirth process and along the lifetime continuum should include identification and treatment for hypertension to promote cardiovascular health.